Answer:
Step-by-step explanation:
we have
E------>the number of sit-ups
m----> the time in minutes
S----> the number of sit-ups after drinking the sports drink
----> equation A
----> equation B
substitute the equation A in the equation B
Answer: y−3=−3y−43
Step 1: Add 3y to both sides.
y−3+3y=−3y−43+3y
4y−3=−43
Step 2: Add 3 to both sides.
4y−3+3=−43+3
4y=−40
Step 3: Divide both sides by 4.
4y
4
=
−40
4
y=−10
Answer:
y=−10
Step-by-step explanation: brainliest:)
I: y<2*x
II: y<8
III: x>2
a: (5,3):
I: 3<2*5
3<10 ?yes
II: 3<8 ?yes
III: 5>2 ?yes
This is a solution
b: (6,0):
I: 0<2*6
0<12 ?yes
II: 0<8 ?yes
III: 6>2 ?yes
This is a solution
c: (3,3):
I: 3<2*3
3<6 ?yes
II: 3<8 ?yes
III: 3>2 ?yes
This is a solution
d: (1,-4):
I: -4<2*1
-4<2 ?yes
II: -4<8 ?yes
III: 1>2 ?no
This is not a solution
e: (4,-2):
I: -2<2*4
-2<8 ?yes
II: -2<8 ?yes
III: 4>2 ?yes
This is a solution
f: (5,9):
I: 9<2*5
9<10 ?yes
II: 9<8 ?no
This is not a solution
so a,b,c,e are solutions and d,f not
Answer:
The functions are inverses; f(g(x)) = x ⇒ answer D
⇒ answer D
Step-by-step explanation:
* <em>Lets explain how to find the inverse of a function</em>
- Let f(x) = y
- Exchange x and y
- Solve to find the new y
- The new y = ![f^{-1}(x)](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29)
* <em>Lets use these steps to solve the problems</em>
∵ ![f(x)=\sqrt{x-3}](https://tex.z-dn.net/?f=f%28x%29%3D%5Csqrt%7Bx-3%7D)
∵ f(x) = y
∴ ![y=\sqrt{x-3}](https://tex.z-dn.net/?f=y%3D%5Csqrt%7Bx-3%7D)
- Exchange x and y
∴ ![x=\sqrt{y-3}](https://tex.z-dn.net/?f=x%3D%5Csqrt%7By-3%7D)
- Square the two sides
∴ x² = y - 3
- Add 3 to both sides
∴ x² + 3 = y
- Change y by ![f^{-1}(x)](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29)
∴ ![f^{-1}(x)=x^{2}+3](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%3Dx%5E%7B2%7D%2B3)
∵ g(x) = x² + 3
∴ ![f^{-1}(x)=g(x)](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%3Dg%28x%29)
∴ <u><em>The functions are inverses to each other</em></u>
* <em>Now lets find f(g(x))</em>
- To find f(g(x)) substitute x in f(x) by g(x)
∵ ![f(x)=\sqrt{x-3}](https://tex.z-dn.net/?f=f%28x%29%3D%5Csqrt%7Bx-3%7D)
∵ g(x) = x² + 3
∴ ![f(g(x))=\sqrt{(x^{2}+3)-3}=\sqrt{x^{2}+3-3}=\sqrt{x^{2}}=x](https://tex.z-dn.net/?f=f%28g%28x%29%29%3D%5Csqrt%7B%28x%5E%7B2%7D%2B3%29-3%7D%3D%5Csqrt%7Bx%5E%7B2%7D%2B3-3%7D%3D%5Csqrt%7Bx%5E%7B2%7D%7D%3Dx)
∴ <u><em>f(g(x)) = x</em></u>
∴ The functions are inverses; f(g(x)) = x
* <em>Lets find the inverse of h(x)</em>
∵ h(x) = 3x² - 1 where x ≥ 0
- Let h(x) = y
∴ y = 3x² - 1
- Exchange x and y
∴ x = 3y² - 1
- Add 1 to both sides
∴ x + 1 = 3y²
- Divide both sides by 3
∴ ![\frac{x + 1}{3}=y^{2}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%20%2B%201%7D%7B3%7D%3Dy%5E%7B2%7D)
- Take √ for both sides
∴ ± ![\sqrt{\frac{x+1}{3}}=y](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cfrac%7Bx%2B1%7D%7B3%7D%7D%3Dy)
∵ x ≥ 0
∴ We will chose the positive value of the square root
∴ ![\sqrt{\frac{x+1}{3}}=y](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cfrac%7Bx%2B1%7D%7B3%7D%7D%3Dy)
- replace y by ![h^{-1}(x)](https://tex.z-dn.net/?f=h%5E%7B-1%7D%28x%29)
∴ ![h^{-1}(x)=\sqrt{\frac{x+1}{3}}](https://tex.z-dn.net/?f=h%5E%7B-1%7D%28x%29%3D%5Csqrt%7B%5Cfrac%7Bx%2B1%7D%7B3%7D%7D)
Answer:
294.5 m²
Step-by-step explanation:
shaded region = area of major sector + area of triangle
central angle of major sector = 360° - 130° = 230°
area of sector = area of circle × fraction of circle
A = π × 11.1² × ![\frac{230}{360}](https://tex.z-dn.net/?f=%5Cfrac%7B230%7D%7B360%7D)
=
≈ 247.3 m²
area of triangle = 0.5 × 11.1 × 11.1 × sin130° ≈ 47.2 m²
shaded area = 247.3 + 47.2 ≈ 294.5 m²